﻿Catalog of the Hydroptilidae (Insecta, Trichoptera) - Robin E. Thomson (ZooKeys, 2023)
The microcaddisfly (Trichoptera: Hydroptilidae) fauna is catalogued from a review of more than 1,300 literature citations through the end of 2020 to include 2,665 currently recognized, valid species in six subfamilies and 76 genera. Fourteen subspecies are included in the total as well as 23 fossil species and three fossil genera. The family Ptilocolepidae (Trichoptera), also covered in this catalogue, comprises 19 valid species in two genera; two subspecies and two fossil species are included in the total. The monotypic genus Eutonella, currently considered incertae sedis within Trichoptera, was formerly placed in Hydroptilidae and is also included in this catalogue. Genus-group and species-group synonyms are listed. Information on the type locality, type depository, sex of type, distribution by country, and other relevant taxonomic or biological information is included for each nominal species. Summary information on taxonomy, phylogeny, distribution, immature stages, and biology are provided for each subfamily, tribe, and genus where known. An index to all nominal taxa is provided to facilitate catalog use.